Evaluation of management control systems in the context of post-merger integration : Case study of PT XLSMART Telecom Sejahtera Tbk in 2025 - Putrie Cynthia Ichwan; Hari Purnomo (PT Wim Solusi Prima, 2026)
This study analyzes the effectiveness of PT XLSMART Telecom Sejahtera Tbk (EXCL)'s management control system in 2025, the first year after the merger between XL Axiata and Smartfren. Using a document analysis approach to four primary data sources, namely the Audited Consolidated Financial Statements, Integrated Annual Reports, Business Sustainability Reports, and the 2025 ESG Report. This study evaluates the management control system through two main theoretical frameworks, namely Simons' Levers of Control and Malmi & Brown's. The findings show that amidst 23.4% revenue growth to IDR 42.45 trillion and the realization of merger synergies of USD 252 million, the company recorded a net loss of IDR 4.41 trillion due to a 45.6% surge in depreciation costs, scattered integration costs, and a dividend policy that is not aligned with actual financial conditions. Meanwhile, the non-financial dimensions show consistent strength. This study concludes that PT XLSMART's management control system experienced symmetric failure because the formal control systems (cybernetic and diagnostic) were inadequate for the complexity of post-merger costs, while cultural and boundary controls functioned effectively. Recommendations are directed at improving the management control system architecture to make it more adaptive to the post-merger transformation phase.